Orthodenticle Homeobox OTX1 Promotes Papillary Thyroid Carcinoma Progression and Is a Potential Prognostic Biomarker - Jing Wei; Xin Wang; Kai Jiao (Genetics Research, 2023)
Papillary thyroid carcinoma (PTC) is the most common type of thyroid neoplasms, characterized by evidence of follicular cell differentiation. Orthodenticle homeobox 1 (OTX1) is a transcription factor which has been implicated in numerous diseases, including malignancies. The objective of this research was to explore the function of OTX1 in PTC. Immunohistochemistry (IHC) was employed to determine the protein level of OTX1 in PTC specimens. Cell viability was assessed by the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. Furthermore, a xenograft model on nude mice was established to investigate in vivo effects of OTX1. Our results revealed that OTX1 was significantly upregulated within specific PTC tissues and was remarkably correlated with unfavorable clinical outcomes in PTC. Silencing OTX1 resulted in a significant inhibition in cell viability and suppressed cell proliferation. In addition, in vivo experiments demonstrated that OTX1 silencing resulted in a significant suppression of tumor growth in nude mice. Collectively, these results suggest that OTX1 may play crucial roles in promoting PTC progression.